2022
DOI: 10.3390/molecules27196450
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of Petroleum Hydrocarbons by Drechsleraspicifera Isolated from Contaminated Soil in Riyadh, Saudi Arabia

Abstract: Currently, the bioremediation of petroleum hydrocarbons employs microbial biosurfactants because of their public acceptability, biological safety, and low cost. These organisms can degrade or detoxify organic-contaminated areas, such as marine ecosystems. The current study aimed to test the oil-biodegradation ability of the fungus Drechslera spicifera, which was isolated from contaminated soil samples in Riyadh, Saudi Arabia. We used hydrocarbon tolerance, scanning electron microscopy, DCPIP, drop-collapse, em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…cubense treated with antifungal hydrocarbons had wrinkled external hyphal surfaces, borders deformity, and ruptured bubbles [ 42 ]. Another study showed that the filamentous fungi D. spicifera showed abnormal morphological changes upon treatments with different petroleum hydrocarbons [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…cubense treated with antifungal hydrocarbons had wrinkled external hyphal surfaces, borders deformity, and ruptured bubbles [ 42 ]. Another study showed that the filamentous fungi D. spicifera showed abnormal morphological changes upon treatments with different petroleum hydrocarbons [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…The tubes were vigorously shaken by vortex to homogenize the contents for 2 min at room temperature. The mixtures were allowed to settle overnight, then the heights of the emulsion layers were measured and proportioned from the total height to estimate the percentage of the emulsification activity, as described before [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As previously stated, the slides were fixed overnight at 4°C with 2.5% Glutaraldehyde, then washed with phosphate buffer (pH 7.2), and re-fixed with 1% Osmium Tetroxide. As previously stated, dehydration in successive dilutions of ethanol, freeze-drying in a critical point drier, and mounting on gold-plated stubs were all completed 52 .…”
Section: Methodsmentioning
confidence: 99%
“…Thus, isolation of such predominant indigenous microorganisms from specific contaminated sites with high degrading ability can act as promising candidate for remediation of contaminated sites (Patowary et al, 2016). Bacterial hydrocarbon degraders like Arthrobacter, Achromobacter, Brevibacterium, Bacillus, Flavobacterium, Pseudomonas, Rhodococcus and Stenotrophomaonas have been reported to degrade certain types of mono or polyaromatic, aliphatic hydrocarbons (Al-Zahrani et al, 2022). Various factors like temperature, nutrients, substrate, aeration play vital roles and should be maintained in favorable conditions to carry out maximum biodegradation.…”
Section: Introductionmentioning
confidence: 99%